A new bacterial white spot syndrome (BWSS) in cultured tiger shrimp Penaeus monodon and its comparison with white spot syndrome (WSS) caused by virus - Wang, Y.G.; Lee, K.L.; Najiah, M.; Shariff, M.; Hassan, M.D. (Inter-Research Science Publisher, 2000)
This paper describes a new bacterial white spot syndrome (BWSS) in cultured tiger shrimp Penaeus monodon. The affected shrimp showed white spots similar to those caused by white spot syndrome virus (WSSV), but the shrimp remained active and grew normally without significant mortalities. The study revealed no evidence of WSSV infection using electron microscopy, histopathology and nested polymerase chain reaction. Electron microscopy indicated bacteria associated with white spot formation, and with degeneration and discoloration of the cuticle as a result of erosion of the epicuticle and underlying cuticular layers. Grossly the white spots in BWSS and WSS look similar but showed different profiles under wet mount microscopy. The bacterial white spots were lichen-like, having perforated centers unlike the melanized dots in WSSV-induced white spots. Bacteriological examination showed that the dominant isolate in the lesions was Bacillus subtilis. The occurrence of BWSS may be associated with the regular use of probiotics containing B. subtilis in shrimp ponds. The externally induced white spot lesions were localized at the integumental tissues, i.e., cuticle and epidermis, and connective tissues. Damage to the deeper tissues was limited. The BWS lesions are non-fatal in the absence of other complications and are usually shed through molting.